2013
DOI: 10.1134/s1064229313050086
|View full text |Cite
|
Sign up to set email alerts
|

The development of chernozems on the Dniester-Prut interfluve in the Holocene

Abstract: The development of forest steppe and steppe chernozems on the Dniester-Prut interfluve in the Holocene was studied on the basis of data on the paleosols buried under archaeological monuments of differ ent ages. The parameters of the mathematic models of the development of the soil humus horizons in differ ent subtypes of chernozems were calculated. They were used to determine the rate of this process and the age of the soils formed on the surface of Trajan's lower rampart. The climate controlled changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Despite this decline, various farms remained active during the Roman and Byzantine periods, apparently focused on gardening [32]. The long-fallowed lands have suffered two phases of humid and dry climate [33] that could affect the conservation of the palaeomorphic features of agrogenesis. When croplands are abandoned, the starting conditions for the restoration process largely depend on the site-specific ecological characteristics (i.e., soil type, climate, former crops, field area, and availability of propagules) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this decline, various farms remained active during the Roman and Byzantine periods, apparently focused on gardening [32]. The long-fallowed lands have suffered two phases of humid and dry climate [33] that could affect the conservation of the palaeomorphic features of agrogenesis. When croplands are abandoned, the starting conditions for the restoration process largely depend on the site-specific ecological characteristics (i.e., soil type, climate, former crops, field area, and availability of propagules) [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, this chernozem is similar or inferior in the abundance of cellulose-degrading microorganisms and characterized by lower activity of the nitrification process. Carbonate chernozems, which are classified as an independent soil subtype in Moldova, are similar to southern chernozems to some extent (Lisetskii et al, 2013). A com-parison of the microbiology of all soils in Moldova (Mehtiev, 1984) showed that carbonate chernozems (with an average 2-2.5% level of CaCO 3 in the upper layer) differ from the subtypes located to the north by the lower abundance of bacteria and fungi, but the larger proportion of actinomycetes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, here is possible to predict a large number o f paths for soils recovery in the lands that have been disturbed by human activity. The change in the rates o f weathering and pedogenesis, which both in Holocene [15][16][17] and in the modem era [18] were due to climatic rhythm, formed the accumulated effect in the geochemical composition of soils and rocks.…”
Section: Resultsmentioning
confidence: 99%